Prelove.UTHM: Second-hand items platform for UTHM community - Tee, Han Boon; Noryusliza Abdullah, (Applied Information Technology And Computer Science, 2023)
Wastage of second-hand items has become an issue in Universiti Tun Hussein Onn Malaysia (UTHM). This issue occurs due to several factors such as lack of specialized platform for selling second-hand items and students that graduate unable to bring everything along with them. Traditional way of selling second-hand items is inefficient since seller need to spend time in finding interested buyer. Therefore, a mobile application named Prelove.UTHM that allows students, staffs and lecturers in UTHM community to sell their second-hand items had been developed. Flutter, Dart and Firebase were applied to design an Android based application using Waterfall methodology. Users can use it to turn their second-hand items into money and buy desired second-hand items easily. Moreover, there is a donation feature to giveaway second-hand items for free. The results of test plan and user acceptance testing show that most of the respondents have high satisfaction while using the application.